Knowledge and practices regarding prevention of peripheral intravenous catheter (PIVC) infection among registered nurses - Nora Sharinaz; Nurul Fariza Muhammad Mustafa; Annamma Kunju Kunju (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Peripheral intravenous catheter (PIVC) cannulation is the insertion of a vascular access device into a peripheral vein. This procedure needs manual skills, professional competency, and knowledge regarding the anatomy and physiology of the vascular system. However, the incidences of PIVC infections occur due to poor cannulation or care post-insertion practices that may lead to prolonged hospital stays. They will increase hospital costs for the patient or the hospital itself. Purpose: To determine Registered nurses' (RN) knowledge and practices regarding PIVC care. Method: This descriptive quantitative study used a set of online questionnaires via Google Forms. These studies aim to determine the knowledge and practice of RNs towards the care and maintenance of PIVC. A total number of 113 respondents have joined this study. Results: Most RNs are well-versed in caring for and sustaining PIVC, while some lack knowledge and practice. Even though just 85.8% of respondents had adequate knowledge, the data revealed that 86.7% followed proper procedures. This could be a source of concern for patient safety. Conclusion: Keywords: Infection; Knowledge; Nurses; PIVC; Practices.